Cement mortars hybridized with zeolite and zeolite-like materials made of lignite bottom ash for heavy metal encapsulation - Kedsarin Pimraksa (2018)
Bottom ash (BA) from Mae Moh lignite power plant was used to synthesize zeolite and zeolite-like materials. Low temperature synthesis (100-110 °C) was completed using SiO 2 to Al 2 O 3 with molar ratios of 2.94 and 2.92, respectively. Factors investigated that affect synthesis include particle size distribution, pretreatment of BA, concentration of alkali solution and liquid to solid ratio. The synthesized product qualities were characterized by mineralogical composition, morphology, specific surface area, pore size, pore volume and cation exchange capacity. Natrolite-K zeolite (NAT-K) was obtained with a solution of BA and 7 M KOH. Zeolite-like material (potassium aluminosilicate hydrate: KASH) was obtained using very fine BA and 9 M KOH solution. The NAT-K, KASH and BA powders were used to replace type I Portland cement at 0, 5,10,20 and 30% by weight to produce composite materials for heavy metal encapsulation. The compressive strength and bulk density of the NAT-K- or KASH-hybridized cement mortars were tested at 1, 7 and 28 days. The heavy metal encapsulation capacity was also tested using the 28-day cement mortar containing either 5 wt% NAT-K or KASH adsorbed with Cr, Ni and Cd ions. The results showed that 5 wt% of NAT-K could improve early strength of cement mortar and the 28-day specimens with 5-10 wt% of NAT-K replacement had compressive strength similar to that of the normal cement mortar. The NAT-K and KASH encapsulate Cr, Ni and Cd ions in the structures of cement mortar matrices more than 97%. © 2012 Elsevier Ltd. All rights reserved.